2018
DOI: 10.1155/2018/2101562
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Increases Insulin Sensitivity and Glutathione Biosynthesis and Protects against Oxidative Stress in a Model of Sucrose‐Induced Insulin Resistance

Abstract: Oxidative stress and redox status play a central role in the link between insulin resistance (IR) and lipotoxicity in metabolic syndrome. This mechanistic link may involve alterations in the glutathione redox state. We examined the effect of glycine supplementation to diet on glutathione biosynthesis, oxidative stress, IR, and insulin cell signaling in liver from sucrose-fed (SF) rats characterized by IR and oxidative stress. Our hypothesis is that the correction of glutathione levels by glycine treatment lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…In the present study, glycine treatment significantly enhanced the nuclear translocation of Nrf2, and increased the mRNA expression of Nrf2‐targeted genes, such as Glo1, CAT, SOD2, HO‐1, NQO1 and GPx‐1, suggesting that the Nrf2 pathway was activated. The activities of SOD and CAT were also increased after glycine treatment, which is consistent with previous studies, but the mechanism remains unclear. One speculation is that glycine increases the level of GSH, which has been reported to increase SOD activity by abolishing reactive oxygen species‐induced inactivation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, glycine treatment significantly enhanced the nuclear translocation of Nrf2, and increased the mRNA expression of Nrf2‐targeted genes, such as Glo1, CAT, SOD2, HO‐1, NQO1 and GPx‐1, suggesting that the Nrf2 pathway was activated. The activities of SOD and CAT were also increased after glycine treatment, which is consistent with previous studies, but the mechanism remains unclear. One speculation is that glycine increases the level of GSH, which has been reported to increase SOD activity by abolishing reactive oxygen species‐induced inactivation.…”
Section: Discussionsupporting
confidence: 91%
“…It was suggested that glycine is rate‐limiting for GSH synthesis. Under diabetes or metabolic syndrome, the level of GSH is reduced, but this reduction can be reversed by glycine treatment. Our previous study showed that the levels of glycine in both serum and kidneys were decreased in diabetic rats, but were restored after oral glycine treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of regulating factors of eNOS expression, such as elevated levels of circulating insulin and insulin resistance (HOMA-IR index) is possibly different in both conditions, since insulin levels and HOMA-IR were increased in LTS rats but not in STS rats. Decreased insulin sensitivity and insulin resistance had already been reported in the MS rats that received the same treatment as our LTS group by using the euglycemic clamp technique [ 54 ]. The severity of the alterations in insulin sensitivity in LTS might trigger compensatory mechanisms that are not initiated in a less severe alteration such as STS.…”
Section: Discussionmentioning
confidence: 76%
“…Glycine has also been observed to help ameliorate metabolic syndrome in obesity and diabetes, with growing evidence that Gly supplementation may have therapeutic benefits through improving insulin sensitivity, enhancing antioxidant capacity, and reducing pro-inflammatory cytokines (reviewed previously by Wang et al, 2013 ). For example, when sucrose feeding was used to induce insulin resistance, rats supplemented with Gly had improved insulin sensitivity and increased hepatic concentrations of GSH, Cys, and γ-glutamylcysteine, which could help reduce oxidative stress ( El-Hafidi et al, 2018 ).…”
Section: Aa Immune Function and Oxidative Stressmentioning
confidence: 99%